Herpes-like eruption due to imiquimod - Pisani, V. (European Journal of Pediatric Dermatology, 2012)
The physical examination of the first (Fig. 1) and the second patient (Fig. 2) may lead to diagnose a herpetic eruption for the presence of multiple crusted, blackish lesions of equal size, sometimes confluent. However, in both cases history tells us that patients after the diagnosis of keratosis have applied excessive amounts of imiquimod, indifferent to the subjective discomfort and the severe cutaneous lesions induced by repeated topical application of imiquimod. In Fig 3 you can see the second patient 15 days after withdrawing imiquimod.